Sanity & Tallulah. 2, Field trip - Brooks, Molly (Molly Grayson) (Disney/Hyperion, 2019)
When Sanity and Tallulah are separated from their classmates during a disastrous field trip to a mining planet, they must rely on their creativity and problem-solving skills to save the day.